W. R. Paton - F.W. Walbank - Craige B. Champìon (Exemplaria Classica, 2010)
W. R. Paton - F.W. Walbank - Chr. Habicht, Polybius, Histories, Book 1-2, trans. W.R. Paton, revised by F.W. Walbank and Chr. Habicht, Cambridge, Mass.: Harvard University Press, 2010, pp. 466. ISBN 978-0-674-99637-3.  W. R. Paton - F.W. Walbank - Chr. Habicht, Polybius, Histories, Book 3-4, trans. W.R. Paton, revised by F.W. Walbank and Chr. Habicht, Cambridge, Mass.: Harvard University Press, 2010, pp. 568, ISBN 978-0-674-99638-0.